What lies at the intersection of law and psychiatric nursing? Exploring the process of judiciarization in the context of mental health - Etienne Paradis-Gagné; Jean-Daniel Jacob; Pierre Pariseau-Legault (York University Libraries, 2020)
In this article, our aim is to provide a critical analysis of the phenomenon of judiciarization of people suffering from a mental illness and its impact on nursing practice. To explore the issues inherent to this phenomenon, we employed the methodology of discursive analysis greatly inspired by the work of French philosopher Michel Foucault. The results of this analysis push our reflection on the experiences and practices that take place at the psychiatric and judicial interface, engaging in a critic of underlying goals of public protection, social control, and coercion being incorporated to nursing practice. While acting in seemingly humanistic and therapeutic roles of care, nurses are simultaneously and inevitably fulfilling a mandate to social control which, to date, remains relatively under documented.